Contacting ultrasound enhanced hot-air convective drying of garlic slices: Mass transfer modeling and quality evaluation. (October 2018) - Tao, Yang; Zhang, Jinglin; Jiang, Sirui; Xu, Yiqun; Show, Pau-Loke; Han, Yongbin; Ye, Xiaosong; Ye, Mingru
Abstract: A self-designed hot-air convective dryer coupled with contacting ultrasound system was used for the dehydration of garlic slices. Contacting ultrasound significantly accelerated the drying process. Compared with non-ultrasound treated samples, the drying time of garlic samples sonicated at 1513.5 W/m 2 was shortened by 35.0% at 50 °C, 48.5% at 60 °C and 50.0% at 70 °C. According to water transport simulation using a diffusion model considering sample shrinkage, both water effective diffusivity and external mass transfer coefficient were enhanced when garlic samples contacted ultrasound directly during drying. In the meantime, internal water diffusion was more affected by contacting ultrasound. Furthermore, contacting ultrasound had a positive effect on the preservation of organosulfur compounds in garlic slices during drying. The browning problem of garlic products during hot-air drying was also alleviated if contacting ultrasound treatment was performed properly. Besides, no over-heating problem was observed during contacting ultrasound enhanced drying within the studied experimental range. Highlights: Contacting ultrasound was used to enhance hot air drying of garlic slices. Drying time was shortened if garlic samples contacted ultrasound directly. Both inner water diffusion and external mass transfer were enhanced by ultrasound. Organosulfur compounds and color of garlic slices were protected by ultrasound. No over-heating was found during contacting ultrasound processing.